1998
DOI: 10.1046/j.1369-6513.1998.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of information‐giving to patients referred for coronary angiography: effects on outcomes of care

Abstract: Objective To assess the impact of providing an educational videotape,`Treatment Choices for Ischaemic Heart Disease: a Shared Decision-Making Program Videotape,' to patients referred for coronary angiography compared with standard patient-physician decision making (usual care). Study design Randomized controlled clinical trial.Setting University Hospital and Veterans A airs Hospital.Patients A consecutive sample of 217 patients referred for coronary angiography were randomized to receive`usual care' or to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 12 publications
(10 reference statements)
3
49
0
1
Order By: Relevance
“…For example, all 9 trials evaluating knowledge have shown that decision aids significantly improve patient knowledge, with a weighted mean difference of 19% (compared with 16% in this trial). 8,[12][13][14][15][16][17][18][19][20] Similarly, all 6 of the trials that examined decisional conflict reported statistically significant improvements with decision aids of magnitudes virtually identical to our results. 17,18,[21][22][23][24] However, decision aids have had variable impacts on management in the 3 tri- als evaluating medical therapies: one 24 reported a 76% increase in hepatitis B vaccination with a decision aid, another 25 reported a nonsignificant 8% reduction in hormone replacement use, and the third 17 reported a nonsignificant 6% increase in ASA use among patients with NVAF at low risk of stroke.…”
Section: Discussionsupporting
confidence: 81%
“…For example, all 9 trials evaluating knowledge have shown that decision aids significantly improve patient knowledge, with a weighted mean difference of 19% (compared with 16% in this trial). 8,[12][13][14][15][16][17][18][19][20] Similarly, all 6 of the trials that examined decisional conflict reported statistically significant improvements with decision aids of magnitudes virtually identical to our results. 17,18,[21][22][23][24] However, decision aids have had variable impacts on management in the 3 tri- als evaluating medical therapies: one 24 reported a 76% increase in hepatitis B vaccination with a decision aid, another 25 reported a nonsignificant 8% reduction in hormone replacement use, and the third 17 reported a nonsignificant 6% increase in ASA use among patients with NVAF at low risk of stroke.…”
Section: Discussionsupporting
confidence: 81%
“…In two other reported randomized trials of SDPs, patients' satisfaction with the decision-making process was also found to be reasonably high. 19,21 In the first study, men with BPH were found to have a mean score for patients' satisfaction with the decision-making process of 76% when exposed to the interactive videodisc, compared with 71% for the control group at 3 months ( P ϭ .03). 19 The clinical significance of this 5% improvement is uncertain and is within the 95% confidence interval of our results.…”
Section: Discussionmentioning
confidence: 99%
“…The mean score for satisfaction with the decision-making process was 75% in both groups. 21 Evidence that the IHD SDP assists in the decisionmaking process is provided by the increase in knowledge. In this study, SDP patients scored significantly higher than controls on the multi-item knowledge scale, with mean scores of 75% and 62%, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations